DEVELOPMENT OF PROJECT-BASED LEARNING-BASED STUDENT WORKSHEETS ONSIMPLE DISTILLATION MAT ERI AT SMPN / MTSN TANAH PINOH - Desy Ramadhani Putri; Rahmat Rasmawan; Maria Ulfah; Hairida Ulfah; Rini Muharini (Jurnal Scientia, 2023)
This study aims to determine the feasibility and response of teachers to project-based learning (PjbL) student work performance (LKPD) on mixed separation material. This research is research and development or R & D (research and development). The development model used is model ADDIE which is adapted into 3 stages, namely analysis (analyze), design (d esign), and development (development). The subject of this study is project-based learning (PjbL) based student work (LKPD). The test subjects in this study involved 6 science teachers, 3 MTSN 1 Tanah Pinoh science teachers, 2 science teachers from SMP IT Imam Syafi'i and 1 science teacher from SMPN 4 Tanah Pinoh. Data collection techniques are carried out through measurement techniques and indirect communication techniques, with assessment instruments, validation questionnaires and response test questionnaires. The feasibility of PJBL-based LKPD is assessed in material, media and language aspects carried out by three experts in each field. Material eligibility was obtained on average 94.7% with the "Very Worthy" criterion, media eligibility (graphicing) obtained an average of 96.4% with the criteria of" Very Worthy", and language eligibility obtained on average 97.9% with the criterion "Very Worthy". Furthermore, the results of the teacher's response to project-based learning (P jBL) LKPD were obtained 90.4% with the "Very Good" criterion. according to the results of the project-based learning (P jBL) Student Worksheet (LKPD) research on mixed separation material is feasible and can be used as teaching materials to support the science learning process, especially in mixed separation materials.